Determinants of desire for children: a multinomial logistic regression approach - Rana, Md. Sohel; Midi, Habshah; Sarkar, Saroje Kumar (Marsland Press, 2013)
World population is a serious dilemma that is growing very fast. Most of the current global crises are the consequences of overpopulation. Overpopulation can result from growth rates driven by high fertility rates. Most of alarming growths are occurring in some Asian countries including Bangladesh. Recent trend of fertility decline in Bangladesh is not enough to attain stable population. The aim of this study is to isolate potential determinants of desire for more children and provide recommendations to eradicate them and accelerating fertility decline to achieve replacement level. Multinomial logit approach efficiently determined few key covariates namely child’s sex preference, professional status, wealth index and residential places of women that are significantly associated with high fertility. Since the potential covariates marked here largely depend on female literacy. Thus the policy makers should pay their attention to ensure the female education and involve them in the workforce to enhance women’s status. Female literacy can reduce poverty and discrimination between sons and daughters to eliminate societal attitudes toward sex preference and resume the further fertility decline.